2017
DOI: 10.1038/cdd.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic repair protects cells from pore-forming toxins by microvesicle shedding

Abstract: Pore-forming toxins (PFTs) are used by both the immune system and by pathogens to disrupt cell membranes. Cells attempt to repair this disruption in various ways, but the exact mechanism(s) that cells use are not fully understood, nor agreed upon. Current models for membrane repair include (1) patch formation (e.g., fusion of internal vesicles with plasma membrane defects), (2) endocytosis of the pores, and (3) shedding of the pores by blebbing from the cell membrane. In this study, we sought to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(179 citation statements)
references
References 55 publications
(83 reference statements)
17
162
0
Order By: Relevance
“…In our model, we propose that differences in charge and length of the pore β-hairpins impact physical properties of the lipid environment that could stimulate activity of mechanosensors, such as caveolin-1 to facilitate MAC removal and recovery from MAC attack. Similarly, membrane repair mechanisms triggered in response to bacterial pore forming toxins may rely on changes in mechanochemical properties of the plasma membrane caused by oligomerized prepores 41 . Although pore forming hairpins of these bacterial homologues extend throughout the bilayer, we speculate that an auxiliary domain’s cholesterol recognition loops that interact with the outer leaflet may serve a similar role as the partially-inserted MAC precursor.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, we propose that differences in charge and length of the pore β-hairpins impact physical properties of the lipid environment that could stimulate activity of mechanosensors, such as caveolin-1 to facilitate MAC removal and recovery from MAC attack. Similarly, membrane repair mechanisms triggered in response to bacterial pore forming toxins may rely on changes in mechanochemical properties of the plasma membrane caused by oligomerized prepores 41 . Although pore forming hairpins of these bacterial homologues extend throughout the bilayer, we speculate that an auxiliary domain’s cholesterol recognition loops that interact with the outer leaflet may serve a similar role as the partially-inserted MAC precursor.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cellular mechanism for assembling multivesicular bodies uses the Endosomal Sorting Complex Required for Transport (ESCRT) of intraluminal vesicles into the endosome (121,122). An ESCRTindependent pathway has been identified that may be ceramide-dependent (123) low, but these levels often increase in disease states or during muscle repair (126), and it has been suggested that their concentration and composition might be used for diagnosis and prognosis (125,127). EV from platelets participate in normal procoagulant activity and thrombin production and their production is crucial for physiologic coagulation (128).…”
Section: Extracellular Vesicles (Ev): Exomeres Exosomes Microparticmentioning
confidence: 99%
“…17 In brief, 2 × 10 6 cells in Ca 2+ Tyrode's buffer were incubated with 20 μg/mL propidium iodide (Sigma-Aldrich, Munich, Germany). 17 In brief, 2 × 10 6 cells in Ca 2+ Tyrode's buffer were incubated with 20 μg/mL propidium iodide (Sigma-Aldrich, Munich, Germany).…”
Section: Ply Permeabilization and Lysis Assaymentioning
confidence: 99%